Sustainable Intensfication of Agriculture 01 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2011)
About 15 years ago, the Rockefeller Science Foundation offered Jim Gockowski the opportunity to work in any five of CGIAR centers. His wife's passion for Africa and Cameroon in particular made the family to choose IITA. In this interview, Gockowski shares his experience as he works in Africa for Africa